Distortion of Gratuities In Acquittal (Vrijspraak) Verdict in Corruption Case Juridical Analysis of the Central Jakarta District Court Decision Number: 37/Pid.Sus-Tpk/2021/PN.Jkt.Pst - Permatasari, Ai; Sirrinawati, Sirrinawati; Gulo, Suarman; Sulaeman, Aep; Wiradirja, Imas Rosidawati (Greenation Research & Yayasan Global Resarch National, 2024)
This study aims to examine and analyze the acts of gratuities givers in the Central Jakarta District Court Decision Number: 37/Pid.Sus-Tpk/2021/PN.Jkt.Pst related to the application of article 5 paragraph (1) letter a and article 13 of law number 31 of 1999 as amended by law number 20 of 2001 concerning the eradication of corruption. This descriptive research uses a normative legal research method through Study Literature legal research using two approaches, namely the statute approach and the case approach. The types of data used are primary data and secondary data. The technique used in the collection of primary legal materials in this study is through literature search by analyzing court decisions, while in secondary legal materials through literature studies and document studies. This study uses a descriptive method analysis technique, namely providing an overview or explanation of the subject, object, and research results, however, the results of this research are not justified by the researcher. The results of this study show that the panel of judges acquitted the defendant, the judge's decision in this case stated that one of the considerations is regarding the absence of a criminal article that regulates the existing act of giving gratuities is the action of the recipient of gratuities, the results of this research are intended to contribute to the literature on gratuities for law enforcement and the eradication of corruption, Unlike the previous research which focused on the application of the article of indictment, this study focuses on the consideration of the Council of Judges about the elements of giving or promising something to a civil servant or state administrator. Using legal political theory and legal findings, this study assesses the legislative policy related to gratuities and the legal interpretation of judges in the condition of legal vacuum. Through a normative and empirical juridical approach, this research produces an in-depth analysis as an academic and practical contribution to the eradication of corruption, especially related to gratuities. The targeted outputs in the form of policy recommendations for regulatory improvement and legal practice guidelines are presented in the form of international journals. The level of research readiness is on an exploratory scale, with the potential for policy implementation.